Pengaruh Motivasi Berwirausaha, Efikasi Diri, Dan Keberanian Mengambil Risiko Terhadap Minat Berwirausaha - Agnesia, Imelga; Pitaloka, Lola Kurnia (Gorontalo State University, 2026)
Economic instability has increased the need for alternative sources of income for households, particularly among housewives who have not been optimally involved in productive economic activities. Entrepreneurship is viewed as an important strategy to enhance household economic independence. This study aims to analyze the effects of entrepreneurial motivation, self-efficacy, and risk-taking propensity on the entrepreneurial interest of housewives in Batang Regency, Central Java. A quantitative approach was employed, with primary data collected through questionnaires distributed to 385 respondents using a simple random sampling technique. The data were analyzed using multiple linear regression with SPSS version 25. The results indicate that entrepreneurial motivation, self-efficacy, and risk-taking propensity partially have positive and significant effects on the entrepreneurial interest of housewives, with entrepreneurial motivation being the most dominant variable. These findings underscore the importance of psychological factors in shaping the entrepreneurial interest of housewives in Batang Regency.